Evaluation and Prioritization of Hospital Management Roles from Experts\' Point of View (Study Case: Imam Khomeini Hospital (RA)) - Rohollh Hosseini; Anis Javanmard (بیمارستان, 2023)
Background: Achieving goals and developing hospital services depends on competence and optimal management. There will be competent managers who can be successful in performing managerial roles. Playing the roles supports the management in the direction of efficiency, administration and optimal management of the hospital. The purpose of this study is to evaluate and prioritize the roles of management in the hospital from the experts' point of view. Materials and Methods: This research has a practical purpose and a descriptive and analytical approach. The statistical sample of the research included 65 experts from Imam Khomeini (RA) Al-Shatar Hospital, who were identified based on the snowball and selective sampling method. In this study, a self-made matrix questionnaire whose validity has been confirmed by experts was used to collect data. TOPSIS technique was used to analyze the data. In this study, five criteria and three main roles, which include 10 secondary roles, were identified Results: The data analysis showed that the promotion of organizational commitment with the percentage of importance (23.2%) with the most important criterion, followed by organizational improvement criteria (20.9%), coordination and coherence (19.4%), promotion of employees' job motivation (7%) 18.00) and improvement of performance efficiency (18.4%) are ranked as effective indicators respectively. Also, the sub-role of analyst supervisor (0.926) was introduced as the most important role among the sub-roles of management in the hospital. Conclusion: Considering that the role of decision-making was introduced as the most important role, as well as the consequences of decisions on the present and future of the hospital, it is necessary for the hospital management to pay more attention and importance to the role of decision-making in order to make optimal decisions.